(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aims to explore the strategic frameworks necessary for navigating the complexities posed by global challenges while aligning with the ambitious goals of Vision 2030. The primary objective is to identify and analyze effective strategic approaches that can be employed by organizations to thrive in an evolving global landscape characterized by economic, environmental, and social uncertainties. To achieve this, the research employs a quantitative methodology, utilizing surveys as the primary data collection tool. A total of 172 participants were surveyed, comprising a diverse sample of stakeholders, including policymakers, business leaders, and academic experts, to ensure a comprehensive understanding of the strategies needed. The findings reveal that organizations that adopt a proactive, adaptive approach to strategy formulation and execution are significantly better positioned to overcome challenges and leverage opportunities associated with Vision 2030. Specifically, the study highlights the importance of fostering collaboration across sectors, investing in technological innovation, and emphasizing sustainability as core components of effective strategic planning. Moreover, the results indicate that organizations that integrate stakeholder feedback into their strategic processes report higher levels of satisfaction and improved outcomes. Based on these insights, the study recommends that organizations prioritize developing flexible strategic frameworks that can be adjusted in response to shifting global dynamics. It also suggests that investing in continuous education and capacity-building for stakeholders is crucial to ensure alignment with Vision 2030 goals. Further, the study advocates for enhanced public-private partnerships to facilitate resource sharing and collective problem-solving. Overall, the research underscores the critical need for a multifaceted and inclusive approach to strategy development, ensuring that organizations are not only reactive but also proactively shaping their futures in alignment with Vision 2030.